2013
DOI: 10.1371/journal.pone.0083572
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Interleukin-18 Polymorphisms -607A/C and -137G/C on Oral Cancer Occurrence and Clinical Progression

Abstract: BackgroundThe purpose of this study was to identify gene polymorphisms of interleukin-18 (IL-18) -607A/C and -137G/C specific to patients with oral cancer susceptibility and clinicopathological status. Methodology and Principal FindingsA total of 1,126 participants, including 559 healthy people and 567 patients with oral cancer, were recruited for this study. Allelic discrimination of -607A/C (rs1946518) and -137G/C (rs187238) polymorphisms of the IL-18 gene was assessed by a real-time PCR with the TaqMan assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 35 publications
(75 reference statements)
1
28
0
Order By: Relevance
“…It was reported that genetic factors play important roles in oral cancer susceptibility, and discovery of potential oral cancer-related SNPs was recommended for the early detection of possible candidates for oral cancer development [9, 1315]. SERPINB5 was reported to be a tumor suppressor by inducing apoptosis and inhibiting proliferation, invasion, and migration of tumor cells [19, 20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that genetic factors play important roles in oral cancer susceptibility, and discovery of potential oral cancer-related SNPs was recommended for the early detection of possible candidates for oral cancer development [9, 1315]. SERPINB5 was reported to be a tumor suppressor by inducing apoptosis and inhibiting proliferation, invasion, and migration of tumor cells [19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…The final volume for each reaction was 10 μL and contained 5 μL of the TaqMan Universal PCR Master Mix, 0.25 μL of the primer/TaqMan probe mix, and 10 ng of genomic DNA. The real-time PCR consisted of an initial denaturation step at 95°C for 10 min followed by 40 cycles consisting of 92°C for 15 s and 60°C for 1 min [15, 17, 18]. The research assistant who conducted the laboratory analyses was blinded to the participants’ diagnoses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The alteration from the "C allele to the "A" allele at site −607C/A and at site −137 G/C alternation from the G allele to the C allele in the (promoter area) were prophesied to be the molecular factor linking sites for the cyclic adenosine monophosphate responsive element between protein and H4TF-1 factor, respectively in addition, polymorphisms of the two positions have been correlated with the activity of IL-18 gene promoter transcription, which can impact the IL-18 expression and, may be, of IFN-γ; these changes in alleles, potentially be the essential mechanism of IL-18 involvement in different diseases [23,24]. IL-18 polymorphism has been shown correlated with different diseases such as oral cancer [10], colorectal cancer [11], thyroid cancer [12], bladder cancer [13], lung cancer [14], and nasopharyngeal carcinoma" [15].…”
Section: Discussionmentioning
confidence: 99%
“…Three types of SNPs of the IL-18 gene in the promoter nucleotides was determined, called −137 G/C (rs187238), −656 G/T or rs1946518, and −607 C/A or rs1946519 [9]. IL-18 gene polymorphisms have shown correlation with different diseases such as oral cancer [10], colorectal cancer [11], thyroid cancer [12], bladder cancer [13], lung cancer [14]. and nasopharyngeal carcinoma [15].…”
Section: Introductionmentioning
confidence: 99%